A typology of cost accounting practices based on activity-based costing - a strategic cost management approach / Gregory Wegmann - Wegmann, Gregory (Universiti Teknologi MARA, Shah Alam: Accounting Research Institute (ARI), 2019)
This article examines cost accounting methods containing one or more activity-based costing (ABC) like dimensions. The objective is to analyze cost accounting proposals with, in part, a philosophy reminiscent ABC. The research purposes are to analyze the strategic dimension of the methods described and to build a typology useful for managers. The discussion leads to a four-dimensional typology based on three strategic objectives assigned to the cost accounting systems. The foundation of the research is the Strategic Cost Management Theory from which emerges the ABC philosophy. The methodology applied is an academic and professional literature review. The typology designed shows common points and similarities of the methods observed and their strategic dimensions. Some of the methods studied are more or less useful for practitioners, according to the situation of their companies.